CHARACTERISTIC OF FLOUR AND MANGROVE (Sonneratia alba) LEAF EXTRACT - Anissa El Ramadhani; N Ira Sari; Santhy Wisuda Sidauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Sonneratia alba is a type of mangrove that has many benefits for life, both ecologically and economically. Processing of S. alba leaves into semi-finished products will increase the utilization of S. alba leaves in the food or feed sector. This study aimed to determine the characteristics of the flour and leaf extract of mangrove S. alba descriptively. The material used in this study was mangrove S. alba leaves taken from Desa Sesap Sesap, Kecamatan Tebing Tinggi, Kabupaten Kepulauan Meranti. The method used in this study was a experimental by conducting the process of making flour and extracts of mangrove S. alba leaves. The results showed that mangrove S. alba leaf flour had a green color, had a fragrant taste, and a coarse texture. Mangrove S. alba leaf extract had a blackish brown color, had astringent or bitter taste, and a rough texture.Keywords: Characteristics, extract, flour, mangrove leaves, S. alba.